Strategi Pemasaran melalui Kegiatan Brand Equity di Media Sosial Instagram - Keysa Jasmine Esvandiary; Raditya Pratama Putra (Bandung Conference Series: Communication Management, 2024)
Abstract. Digital payment platforms like IndibizPay, which are specifically designed to support MSMEs in adopting digital payments, have a great opportunity to leverage social media as a tool for building brand image. The aim of this research is to explore and understand how IndibizPay utilizes social media in building a brand image through programs, types of services, and reasons for marketing communications. The method in this research is qualitative using a case study approach. Researchers conducted interviews with the IndibizPay team and users. The results of this research show that: (1) Through these various initiatives, IndibizPay has succeeded in expanding its brand reach, increasing engagement, and building deeper relationships with its community. This IndibizPay program includes business webinars, weekly giveaways, collaboration with content creators via Instagram live streaming, and blog competitions with attractive prizes. (2) IndibizPay has prioritized creating fast QRIS as a superior service that differentiates them from similar competitors, strengthening its image as a service innovator digital finance and strengthen relationships with users.(3) IndibizPay adopts marketing communications through social media to strengthen brand equity, recognizing the importance of a deep understanding of the impact of social media in a rapidly evolving digital era Abstrak. Platform pembayaran digital seperti IndibizPay, yang dirancang khusus untuk mendukung UMKM dalam mengadopsi pembayaran digital, memiliki peluang besar untuk memanfaatkan media sosial sebagai alat untuk membangun citra merek. Tujuan penelitian ini adalah untuk menggali dan memahami bagaimana IndibizPay memanfaatkan media sosial dalam membangun citra merek melalui program, jenis layanan, dan alasan komunikasi pemasaran. Metode dalam penelitian ini adalah kualitatif dengan menggunakan pendekatan studi kasus. Peneliti melakukan wawancara terhadap tim IndibizPay dan pengguna. Hasil penelitian ini menunjukkan bahwa: (1) Melalui berbagai inisiatif ini, IndibizPay berhasil memperluas jangkauan mereknya, meningkatkan interaksi, dan membangun hubungan yang lebih dalam dengan komunitasnya. Program IndibizPay ini mencakup webinar bisnis, giveaway mingguan, kolaborasi dengan content creator melalui Instagram livestreaming, dan kompetisi blog dengan hadiah menarik.(2) IndibizPay telah memprioritaskan pembuatan QRIS cepat sebagai layanan unggulan yang membedakan mereka dari pesaing sejenis, mengukuhkan citra sebagai inovator layanan keuangan digital dan memperkuat hubungan dengan pengguna.(3) IndibizPay mengadopsi komunikasi pemasaran melalui media sosial untuk memperkuat brand equity, mengenali pentingnya pemahaman mendalam tentang dampak sosial media dalam era digital yang berkembang pesat.